On the quasi-static effective behaviour of poroelastic media containing elastic inclusions. (March 2019) - Royer, Pascale; Recho, Pierre; Verdier, Claude
Highlights: The behaviour of a poroelastic medium with elastic inclusions is poroelastic. The effective parameters are strongly affected by the inclusions. The impact on fluid flow is strictly geometrical. Abstract: The aim of the present study is to derive the effective quasi-static behaviour of a composite medium, made of a poroelastic matrix containing elastic impervious inclusions. For this purpose, the asymptotic homogenisation method is used. On the local scale, the governing equations include Biot's model of poroelasticity in the porous matrix and Navier equations in the inclusions, with elastic properties of the same order of magnitude. Biot's diphasic model of poroelasticity is obtained on the macroscopic scale, but with effective parameters that are strongly impacted by the distribution of inclusions, even at low volume fraction. The impact on fluid flow is strictly geometrical, showing that the inclusions do not play the role of a porous network.